Electrochemical Synthesis of Carbon Quantum Dots - Rocco, Daniele; Moldoveanu, Vyali Georgian; Feroci, Marta; Bortolami, Martina; Vetica, Fabrizio (ChemElectroChem, 2023)
Carbon quantum dots (CDs) are “small” carbon nanostructures with excellent photoluminescence properties, together with low‐toxicity, high biocompatibility, excellent dispersibility in water as well as organic solvents. Due to their characteristics, CDs have been studied for a plethora of applications as biosensors, luminescent probes for photodynamic and photothermal therapy, fluorescent inks and many more. Moreover, the possibility to obtain carbon dots from biomasses and/or organic waste has strongly promoted the interest in this class of carbon‐based nanoparticles, having a promising impact in the view of circular economy and sustainable processes. Within this context, electrochemistry proved to be a green, practical, and efficient method for the synthesis of high‐quality CDs, with the possibility to fine‐tune their characteristics by changing operational parameters. This review outlines the principal and most recent advances in the electrochemical synthesis of CDs, focusing on the electrochemical set‐up optimization. Critical biography: Carbon dots (CDs) are an important class of carbon nanoparticles featured by a vast range of applications, paired with low toxicity. Due to these reasons, the development of synthetic methodologies to obtain high‐quality carbon dots is of pivotal importance. This review outlines the electrochemical methodologies for the synthesis of CDs reported over the years, with a detailed analysis on how the electrochemical parameters could tune the nanodots properties.